ANALYSIS OF CAPITAL ADEQUACY RATIO, FINANCING TO DEPOSIT RATIO, OPERATIONAL COSTS OPERATIONAL REVENUE, AND NON PERFOMING LOAN ON PROFITABILITY OF BANK RAKYAT INDONESIA MAKASSAR BRANCH - Stephanie Aurea Mettha Puspita; Syamsu Alam; Erlina pakki (Scientium Management Review, 2023)
This study aims to examine and find out how the effect of Capital Adequacy Ratio (CAR), Financing to Deposit (FDR), Operating Income Operational Costs (BOPO), and Non-Performing Loans (NPL) on Return On Assets (ROA) at Bank BRI Makassar Branch. . This research is a quantitative research by analyzing ratios and using multiple linear regression analysis. The results show that the CAR variable has no significant and negative effect on ROA, this is because high CAR used to cover the risk of loss or assets that contain risks can reduce the bank's ability to expand its business. FDR has a positive and significant effect on ROA, which means that increased FDR absorption can cause ROA to increase and the increase in the number of loans given by banks will increase the level of public confidence. BOPO has a significant and negative effect on ROA, which means a low BOPO ratio so that banks can minimize operational risks derived from the large value of operating income. NPL has a significant and negative effect on ROA, this shows that the increasing number of non-performing loans makes banks not dare to increase lending, especially since the total third party funds received by banks are not optimal, causing bank liquidity to be disrupted. However, CAR, FDR, BOPO and NPL show that simultaneously or simultaneously have an effect on ROA with a determinant value of 0.82%.